Perlindungan Penata Laksana Rumah Tangga (PLRT) Indonesia - Hengki Firmanda; Andre Antonius (Jurnal Hukum Respublica, 2020)
Protection of migrant workers, especially those working in informal areas, has become a serious problem in several countries, including Indonesia. Informal migrant workers such as domestic helpers, including one of the areas that get the most attention because of the lack of protection afforded to them. The rights of migrant workers are often violated only for the sake of economic benefits to both sending and receiving countries. This condition makes the government of each country should seriously think about the social protection of migrant workers. informal migrant workers were limited into consideration in discussions related to the social protection of labor, even though they work in the working area that very vulnerable to exploitation. This paper will examine qualitatively the comparative law approach to the problem of informal social protection of migrant workers between Indonesia and Malaysia. The results showed that the legal status of migrant workers are often not regulated informally legislation in the host country (Malaysia) that their protection does not exist in law or in practice, in addition to the problems of bureaucracy and politics also became an obstacle for domestic workers in getting access to social protection.